1989
DOI: 10.2113/gsecongeo.84.5.1417
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of gray monazites; evidence from the Paleozoic of Belgium

Abstract: Systematic mineralogical investigations, carried out on panned stream concentrates from the northwestern part of the Cambro-Ordovician Stavelot massif (Belgium), led to the discovery of nodular gray monazites. These were later identified in situ in black slates associated with conglomeratic levels containing phosphatic material. Microscopic investigation shows that gray monazites are authigenic and predate cleavage. To test the hypothesis of a sedimentary origin for rare earth elements, samples of shales, phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 7 publications
1
18
0
8
Order By: Relevance
“…Neodymium shows the greatest variation of the MREE, from $19 wt% Nd 2 O 3 in the cores to $10% in the rims, while La 2 O 3 ranges from $8 wt% in the cores to $18 wt% in the rims. The monazite grains have elevated Eu 2 O 3 values ($0.5 wt% in the cores; $0.15 wt% in the rims), which are typical of monazites from slate belts (Rosenblum and Mosier, 1983;Burnotte et al, 1989;Cabella et al, 2001) and other low-temperature settings.…”
Section: Monazite Geochemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…Neodymium shows the greatest variation of the MREE, from $19 wt% Nd 2 O 3 in the cores to $10% in the rims, while La 2 O 3 ranges from $8 wt% in the cores to $18 wt% in the rims. The monazite grains have elevated Eu 2 O 3 values ($0.5 wt% in the cores; $0.15 wt% in the rims), which are typical of monazites from slate belts (Rosenblum and Mosier, 1983;Burnotte et al, 1989;Cabella et al, 2001) and other low-temperature settings.…”
Section: Monazite Geochemistrymentioning
confidence: 97%
“…Monazite has long been considered to be thermodynamically unstable during diagenesis and sub-amphibolite facies metamorphism (Overstreet, 1967), however, a number of recent studies have identified monazite growth during diagenesis (Burnotte et al, 1989;Milodowski and Zalasiewicz, 1991;Lev et al, 1998), prehnitepumpelleyite facies metamorphism (Cabella et al, 2001;Rasmussen et al, 2001Rasmussen et al, , 2005 and greenschist facies metamorphism (Franz et al, 1996;Rasmussen et al, 2002;Wing et al, 2003).…”
Section: Growth Of Prehnite-pumpellyite Facies Monazitementioning
confidence: 99%
“…Otherwise, Sm invariably is subordinate to minor with respect to the major REE, as is Gd. This is abundantly documented in general reviews of monazite (e.g., Neumann et al 1966, Fleischer & Altschuler 1969, as well as in statistically extensive studies of monazite from a variety of specific petrological environments: granitic suites, granitic pegmatites, tin deposits, Alpine fissures, sediments and metamorphic rocks (e.g., Lee & Bastron 1967, Donnot et al 1973, Petruk & Owens 1975, Burnotte et al 1989, Wark & Miller 1993, Watt 1995, Förster & Rhede 1995, Franz et al 1996, van Emden et al 1997, Förster 1998. What may be the reason for the unique enrichment of the Annie Claim #3 monazite-(Sm) in Sm and Gd?…”
Section: Geochemical Considerationsmentioning
confidence: 83%
“…Detrital monazite texture, mode of occurrence and its geochemistry have been found to point toward its genetic environment, therefore, enabling separation of igneous monazite from its hydrothermal counterpart (buRnotte et al, 1989;scHandl et al, 1994;WanG et al, 1994). scHandl & GoRton (2004 demonstrated that hydrothermal monazite can be distinguished from igneous monazite by combining petrographic analyses with advanced electron microscopy techniques, performed on monazite mineral grains, and concluded that hydrothermal monazite (or greenschist-amphibolite metamorphic facies monazite) generally contains lower concentrations of ThO 2 (< 1 wt%), compared to igneous monazite, in which concentrations of ThO 2 were found to be significantly higher (3 ->5 wt%).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of drainage area and therefrom eroded rocks, of the river and its tributaries combined with in-detail chemical analyses of minerals, both from parent rock and sediments, is crucial for determining the provenance of the grains downstream. The region of Hohe Tauern, in detail discussed by scHiMd et al (2013) andscHaRF et al (2013), is considered to be the source of gold found in fluvial sediments of river Drava (beRManec et al, 2014), therefore broader area of Hohe Tauern could also be considered as a source of minerals in heavy mineral sands.…”
Section: Geographical and Geological Backgroundmentioning
confidence: 99%